Comparison between autogenous welding and with addition of nickel on nd:yag pulsed laser welded UNS s32750 duplex stainless steel - Da Cruz, Eli Jorge (2019)
Duplex stainless steels (DSS) have a biphasic microstructure with equal proportions of austenite and ferrite, which gives them excellent mechanical strength and corrosion resistance compared to austenitic stainless steels. Nd:YAG pulsed laser welding affects the microstructure of DSS resulting in unbalanced microstructure which compromises their properties. As way to obtain a balanced microstructure we have the addition of austenite forming elements, such as nickel or nitrogen. The present work reports the effect of nickel addition on the microstructure and microhardness of UNS S32750 duplex stainless steel welded by Nd:YAG pulsed laser. Two conditions were used: Autogenous welding and with addition of nickel (electrolytic nickel foil with 30 μm thickness placed on the contact surface of weld joint). The addition of nickel affected both the microstructure and microhardness resulting in equal proportions of austenite and ferrite in the weld bead and decreased the microhardness in comparison to autogenous.